A national cross-sectional study of exposure to outdoor nitrogen dioxide and aeroallergen sensitization in Australian children aged 7–11 years. (15th February 2021) - Tu, Yanhui; Williams, Gail M.; Cortés de Waterman, Adriana M.; Toelle, Brett G.; Guo, Yuming; Denison, Lyn; Babu, Giridhara R.; Yang, Bo-Yi; Dong, Guang-Hui; Jalaludin, Bin; Marks, Guy B.; Knibbs, Luke D.
Abstract: The prevalence of allergic diseases in Australian children is high, but few studies have assessed the potential role of outdoor air pollution in allergic sensitization. We investigated the association between outdoor air pollution and the prevalence of aeroallergen sensitization in a national cross-sectional study of Australian children aged 7–11 years. Children were recruited from 55 participating schools in 12 Australian cities during 2007–2008. Parents completed a detailed (70-item) questionnaire. Outdoor nitrogen dioxide (NO2 ), as a proxy for exposure to traffic-related emissions, was estimated using measurements from regulatory monitors near each school and a national land-use regression (LUR) model. Three averaging periods were assessed, using information on duration of residence at the address, including lifetime, previous (lifetime, excluding the last year), and recent (the last year only). The LUR model was used as an additional source of recent exposure estimates at school and home addresses. Skin prick tests (SPTs) were performed to measure sensitization to eight common aeroallergens. Multilevel logistic regression estimated the association between NO2 and sensitization (by individual allergens, indoor and outdoor allergens, and all allergens combined), after adjustment for individual- and area-level covariates. In total, 2226 children had a completed questionnaire and SPT. The prevalence of sensitization to any allergen was 44.4%. Sensitization to house dust mites (HDMs) was the most common (36.1%), while sensitization to Aspergillus was the least common (3.4%). Measured mean (±s.d.) NO2 exposure was between 9 (±2.9) ppb and 9.5 (±3.2) ppb, depending on the averaging period. An IQR (4 ppb) increase in measured previous NO2 exposure was associated with greater odds of sensitization to HDMs (OR: 1.21, 95% CI: 1.01–1.43, P = 0.035). We found evidence of an association between relatively low outdoor NO2 concentrations and sensitization to HDMs, but not other aeroallergens, in Australian children aged 7–11 years. Graphical abstract: Image 1 Highlights: Air pollution may affect aeroallergen sensitization, but evidence is inconsistent. We performed a national cross-sectional study of Australian children. We found that outdoor NO2 was associated with sensitization to house dust mites. We did not find associations between NO2 and other aeroallergens. Abstract : We have added new results to the relatively scarce evidence base on the effects of low-level urban air pollution and aeroallergen sensitization in children.